Problems and questions concerning the self-defence provision (Academic Journal of Internal Affairs, 2024)
The author provides an overview of the practical issues the self-defence provisions of the new Hungarian Criminal Code raise.
Keywords: new justifiable defence; preventive justifiable defence; legislation